Climate Change in the Arab World: How can the region turn its environmental challenges into opportunities? - Joe Y. Battikh (Fiker Institute, 2022)
Due to their geographical location and climate conditions, Arab states have some of the highest wind and solar energy capacities in the world. Increased awareness of this region-wide potential can usher in a new era for Arab states to work more collectively on advancing joint sustainability efforts. With Egypt hosting COP27 this year, and the United Arab Emirates (UAE) hosting COP28 in 2023, the time could not be more pressing and opportune.